Comparison of Intrathecal Midazolam and Fentanyl Added to Bupivacaine for Spinal Anesthesia in Patients Undergoing Appendicectomy - Thapa, Puja; Panta, Sunita; Amatya, Biswo Ram; Rayamajhi, Mallika (Nepalese Medical Journal, 2020)
Introduction: Hyperbaric Bupivacaine is the extensively used local anesthetic but the major disadvantage is profound sympathetic blockade leading to hypotension and prolonged duration of motor block. The addition of Fentanyl or Midazolam can provide excellent quality and prolong the duration of analgesia. The study aims to compare the effect of intrathecal Fentanyl with that of intrathecal Midazolam in combination with 0.5% hyperbaric Bupivacaine on the duration and quality of spinal anesthesia in patients undergoing appendicectomy. Materials and Methods: This is a prospective, comparative and interventional study where patients were randomized into two equal groups. The study was conducted in a tertiary referral hospital from July 2018 to December 2018 after ethical approval. Group BF received Fentanyl and group BM received Midazolam The outcomes measured were, peak sensory level, quality of intraoperative analgesia and motor block, duration of effective analgesia, intraoperative and postoperative complications. Results: A total of 44 patients were studied with 22 in each arm. The two groups were comparable in terms of age, weight, height, duration of surgery, and ASA status of the patients. Peak sensory level and degree of motor block were not statistically different in the two arms. Duration of effective analgesia was 293.16±35 min in the BF group and 267.80±32 min in the BM group (p=0.01). Increased incidence of pruritus was recorded during the postoperative period in the Fentanyl group. Conclusions: Fentanyl and Midazolam both are equally effi cient adjuvant added to hyperbaric Bupivacaine for intrathecal use to improve the quality of spinal anesthesia in patients undergoing appendicectomy.